STRATEGI PAIKEM TIPE CERAMAH PLUS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN AL-QUR’AN-HADITS DI MADRASAH IBTIDAIYAH MA’HAD ISLAMI PALEMBANG - Elhefni Elhefni; Ahmad Syarifuddin (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2014)
The pretest result of an experimental group in al-Qur’an-Hadits subject on Tajwid material before PAIKEM strategy type lecturing plus (lecturing, singing, memorizing, and bribing) was implemented at Madrash Ibtidaiyah (MI) Ma’had Islami Palembang was at fair category or there were 20 students (71%) from 28 students that were taken as a sample. Moreover, there were 23 students (82%) at fair category from 28 students that were taken as a sample. Additionally, after comparing t value (to = 2,12) and t table (tt.ts.5% = 2.05 dan tt.ts. 1% = 2,77) it was found that to is higher than tt ; it was 2,05<2,12<2,77. Finally, because of that to is higher than tt it can be concluded that null hypothesis is rejected. It means that there was a significant different between the students who were taught before implementing PAIKEM strategy type lecturing plus and after implementing it.